Higher risk of major adverse cardiac events after acute myocardial infarction in patients with schizophrenia. Issue 2 (29th September 2020) - Attar, Rubina; Wester, Axel; Koul, Sasha; Eggert, Svend; Polcwiartek, Christoffer; Jernberg, Tomas; Erlinge, David; Andell, Pontus
Abstract : Background: Patients with schizophrenia are a high-risk population due to higher prevalences of cardiovascular risk factors and comorbidities that contribute to shorter life expectancy. Purpose: To investigate patients with and without schizophrenia experiencing an acute myocardial infarction (AMI) in relation to guideline recommended in-hospital management, discharge medications and 5-year major adverse cardiac events (MACE: composite of all-cause mortality, rehospitalisation for reinfarction, stroke or heart failure). Methods: All patients with schizophrenia who experienced AMI during 2000–2018 were identified (n=1008) from the nationwide Swedish Web-system for Enhancement and Development of Evidence-based care in Heart disease Evaluated According to Recommended Therapies registry and compared with AMI patients without schizophrenia (n=2 85 325). Kaplan-Meier survival curves and multivariable Cox regression models were used to compare the populations. Results: Patients with schizophrenia presented with AMI approximately 10 years earlier (median age 64 vs 73 years), and had higher prevalences of diabetes, heart failure and chronic obstructive pulmonary disease. They were less likely to be invasively investigated or discharged with aspirin, P2Y12 inhibitors, ACE inhibitors/angiotensin II receptor blockers, beta-blockers and statins (all p<0.005). AMI patients with schizophrenia had higher adjusted risk of MACE (aHR=2.05, 95% CI 1.63 to 2.58), mortality (aHR=2.38, 95% CI 1.84 to 3.09) and hospitalisation for heart failure (aHR=1.39, 95% CI 1.04 to 1.86) compared with AMI patients without schizophrenia. Conclusion: Patients with schizophrenia experienced an AMI almost 10 years earlier than patients without schizophrenia. They less often underwent invasive procedures and were less likely to be treated with guideline recommended medications at discharge, and had more than doubled risk of MACE and all-cause mortality. Improved primary and secondary preventive measures, including adherence to guideline recommendations, are warranted and may improve outcome.